Anak Digital Native dan Krisis Kontrol Diri: Analisis Parenting Style terhadap Paparan Judi Online pada Siswa SD dan SMP - Ai Sela Silpiani; Nova Fitriani; Davina Avrilyanisa; Hilman Taufiq Abdillah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to analyze the influence of parenting style and self-control on online gambling exposure among elementary and junior high school students from a legal and Islamic perspective. The increasing exposure to online gambling among digital native children indicates self-control issues caused by a lack of digital supervision from families and high access to indirect gambling content on social media and online games. This study used a mixed method with a simultaneous triangulation design involving 102 elementary and junior high school students as respondents, as well as interviews with teachers and parents. The findings of the study indicate that parenting style and self-control have a significant influence on online gambling exposure, both separately and simultaneously. The coefficient of determination value of 56% indicates that these two variables make a strong contribution in explaining the level of online gambling exposure among students. This study also highlights that low digital literacy among parents, weak emotional regulation in students, and the influence of the digital environment are the main factors that increase children’s risk of online gambling. From an Islamic perspective, this phenomenon is contrary to the principles of Maqāṣid al-Sharīʿah, especially in protecting reason, property and offspring.